2020
DOI: 10.1186/s12887-020-02194-7
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study on caregivers’ perspective of the quality of life and adherence of paediatric HIV patients to highly active antiretroviral therapy

Abstract: Background: Poor compliance to highly active antiretroviral therapy (HAART) can result in the poor quality of life in children living with Human immunodeficiency virus/Acquired immunodeficiency syndrome (HIV/AIDS) because of low plasma drug concentration and the possibility of drug resistance. This study evaluates the response of caregivers for determination of adherence and the four quality of life domains in children (aged 14 years and under) on HAART. Methods: We conducted a cross-sectional study of 188 chi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
2
1
Order By: Relevance
“…The significance of family and social support in managing chronic diseases is well-established, often positively impacting healthrelated QoL [24]. Studies across various chronic conditions like hypertension and HIV have linked effective disease management to living within a nuclear family structure [25][26][27][28]. However, in our study focusing on FMF, we found no significant difference in family structure concerning family support.…”
Section: Discussioncontrasting
confidence: 73%
“…The significance of family and social support in managing chronic diseases is well-established, often positively impacting healthrelated QoL [24]. Studies across various chronic conditions like hypertension and HIV have linked effective disease management to living within a nuclear family structure [25][26][27][28]. However, in our study focusing on FMF, we found no significant difference in family structure concerning family support.…”
Section: Discussioncontrasting
confidence: 73%
“…The MONOD ANRS 12206 cohort showed that fathers as caregivers were risk factors for VF (28). Other studies from resource-limited countries also reported that the age, marital status, and physical health of caregivers were risk factors associated with adherence (29)(30)(31). It suggested that there was a direct influence between children's adherence to antiretroviral therapy and their caregivers.…”
Section: Discussionmentioning
confidence: 95%
“…Likewise, studies conducted in Africa have shown that non-disclosure of children's HIV status by caregivers has influenced ART adherence among children negatively. [32][33][34] Hence family caregivers have complained of children's refusal to take ART because, in a longitudinal observational cohort study, a child's awareness of his/her HIV status is an influencing factor in adherence to ART. 27 Children with information about their HIV status adhere to ART better than children without knowledge of their HIV status.…”
Section: Discussionmentioning
confidence: 99%